The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1155/2015/287398
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Quilting Technique for Reduction of Postmastectomy Seroma: A Randomized Controlled Study

Abstract: Background. Postmastectomy seroma causes patients' discomfort, delays starting the adjuvant therapy, and may increase the possibility of surgical site infection. Objective. To evaluate quilting of the mastectomy flaps with obliteration of the axillary space in reducing postmastectomy seroma. Methods. A randomized controlled study was carried out among 120 females who were candidates for mastectomy and axillary clearance. The intervention group (N = 60) with quilting and the control group without quilting. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 21 publications
5
46
0
Order By: Relevance
“…The mechanism of action most likely involves is reduction in dead space; however, the reduction in postoperative discomfort could have reduced patient interference with the incision and, thus, prevented seroma formation. These findings are similar to those identified in human patients after abdominoplasty and mastectomy procedures, in which quilting suture patterns have been shown to reduce the incidence of postoperative seroma substantially …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The mechanism of action most likely involves is reduction in dead space; however, the reduction in postoperative discomfort could have reduced patient interference with the incision and, thus, prevented seroma formation. These findings are similar to those identified in human patients after abdominoplasty and mastectomy procedures, in which quilting suture patterns have been shown to reduce the incidence of postoperative seroma substantially …”
Section: Discussionsupporting
confidence: 86%
“…This technique anchors the subcutaneous tissues to the abdominal wall. The proposed benefits of quilting include the elimination of dead space, thereby reducing seroma formation and surgical site infection (SSI) . Potential disadvantages include increased postoperative discomfort and prolonged surgery with no benefit to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the amount of seroma required aspiration among patients treated with both arm technique, this study was comparable with several authors who showed significantly less drainage in the quilting group when compared to the nonquilting group [28][29][30]. There was significant association between presence of seroma and level of clearance this may be due to removal of a larger number of lymph nodes which results in greater injury of the lymph vessels.…”
Section: Role Of Quilting Technique Of Mastectomy Flap In Prevention supporting
confidence: 83%
“…The technique of obliteration of dead space, therefore seem to be advantageous by tacking of mastectomy flaps to the pectoralis muscle and fascia. Several authors also reported that the incidence of seroma was significantly lower in the quilting group compared with the non-quilting group [28][29][30].…”
Section: Role Of Quilting Technique Of Mastectomy Flap In Prevention mentioning
confidence: 99%
“…Several strategies have been attempted and described in order to reduce the incidence of seroma [8][9][10][11]. Some of the most commonly applied strategies are watchful waiting, compressive dressings or puncture and aspiration [12].…”
Section: Discussionmentioning
confidence: 99%